A Test of Two Empirical Evapo-transpiration Formulae for Semi-Arid Regions - Mahalaxshmi, V F; Ahmed, M F; Rao, K P; Bidinger, F R (Annals of Arid Zone, 2016)
Potential evapo-transpiration (PET) data are required for a number of climatic analyses. As measured PET values arc seldom available. particularly in historical climate data sets. it is necessary to estimate PET from available climatic data. which arc often limited to rainfall and temperature in ordinal)'. rural meteorological observatories. Simple empirical PET estimation procedures. even though generally location or region specific. are often the only alternative. In this study we compared open pan evaporation and estimates of daily PET from two empirical formula viz . Linacre and Campbell (a modified Priestly-Taylor formula). with PF:r estimates by the Penman formula. usually considered the most accurate PET formula. for five diverse arid and semi-arid locations in India. Estimates of PET fromula Linacre equation were (I) generally more linearly correlated with Pennwn estimates of PET. and (2) the standard deviations of the difference between Linaere and Penman estimates were lower. relative to similar comparison between either open pan evaporation or Campbell PET estimates and Penman PET. Estimates of PET by the Linaere formula were consistently higher than the Penman equation estimates. but with an appropriate calibration factor. derived from a few years of complete weather data, the Linacre formula can he used to estimate PET for semi-arid locations where input data for the Penman equation arc not available.